Virulence changes in Vibrio parahaemolyticus during the freezing of Penaeus chinensis - Zenghui Gao; Heer Ding; Ke Li; Qiang Zhang; Xubo Zhao; Liu Bin; Tianli Yue (Food Science and Human Wellness)
Although Vibrio parahaemolyticus has become the most common pathogen in fresh and frozen seafood, its virulence changes have often been ignored during the processing of seafood. To investigate these potential risks, we used frozen Penaeus chinensis as examples, and the most virulent factors of V. parahaemolyticus, including amounts, VBNC status, toxins TDH and TRH, and virulence genes tdh and trh, were determined. Bacterial quantities were significantly reduced during drain and sprinkling phases, but caused by different factors. By SYTO9 and PI staining showed that washing was the main reason for the bacterial reduction at the drain phase, while the strain entering VBNC state was another reason at sprinkling phase. Their hemolysis toxicity, produced by TDH and TRH, became stronger after inoculation on shrimp, and could be detected throughout the process. Moreover, tdh and trh also exhibited trends similar to that of the hemolysis toxicity test. tdh was almost to a two-fold expression level during ice-glazing phase, while trh only express at a low level, less than half of the expression level before inoculation. These results demonstrated that the strains were not dead during freezing process, but became VBNC cells, which still produced and accumulated toxins, especially TDH, the most virulent factor.